Phosphorus skipping effect on productivity, profitability and sustainability of rice-wheat cropping systems in Indo-Gangetic plains of India. Issue 8 (3rd July 2019) - Tripathi, Subhash Chandra; Chander, Subhash; Meena, Raj Pal
ABSTRACT: A field experiment was conducted for eight years at ICAR-Indian Institute of Wheat and Barley Research, Karnal, Haryana, India to study the skipping effect of P application on productivity, profitability and sustainability of rice-wheat cropping system. Rice yield and biomass were 8.35% and 6.6% higher where cowpea was grown after wheat compared to rice-vegetable pea-wheat crop sequence, respectively. Phosphorus application to rice or wheat or both crops exhibited at par rice grain yield, biomass, harvest index. Phosphorus application to both crops or only in rice crop produced maximum and significantly higher wheat yield (4.62 t ha −1 ) as compared to P application only to wheat (4.48 t ha −1 ). Eight years growing of green gram, cowpea and vegetable pea increased the organic carbon content 42.89, 16.38 and 4.57 %, respectively compared to the initial level. Skipping of P to either crop, by considering 13.5 million ha rice-wheat area, will save approximately Rs 40, 500 million (Rs = Indian rupee) or US $ 623 million ($ = Rs 65) per year. Air pollution may be checked, due to saving on diesel in transportation of P fertilizer, to the tune of 60, 383 tonnes of CO2 per year by reducing emission of one of important global warming gas.